Competition for Social Status in the Indigenous North Toraja Communities (A Study in Tondon Matallo Village, Tondon District, North Toraja District) - Ferdinand Kerebungu; Senden Sakka; Veronika E. T. Salem; Siti Fathimah (Jurnal Mamangan, 2024)
This research delves into the social status competition observed in Tondon Matallo. The primary focus of the competition revolves around the pricing and quantity of buffaloes purchased and slaughtered during this significant ceremony. Notably, the acquisition of a substantial number of buffaloes, often involving significant financial investment, does not necessarily alter individuals' social status. Consequently, the study aims to elucidate the dynamics of social status competition and identify the factors influencing it in North Toraja, employing Lewis Coser's conflict theory. Adopting a qualitative research methodology. The findings show that social values that previously focused on aspects of togetherness are now prioritised. The rambu solo becomes the main stage for economic competition. The dynamics of social interaction have become more structured and focused on aspects related to competition, creating relationship dynamics that are different from everyday situations. Perceptions of social status that were previously influenced by age, wisdom or positive contributions to the community, are now more related to the financial ability to purchase and slaughter buffalo, creating a shift in perceptions of what is considered prestigious and contributes to social status. As such, social values that previously focussed on aspects of togetherness have shifted during the rambu solo ceremony creating a new perspective on how cultural change can affect community dynamics. This reflects an evolution in the values recognised and valued by the community during such special events.